Investigation on the uncertain factors of the elastic–plastic contact characteristics of the planetary roller screw mechanism. (March 2019) - Yao, Qin; Liu, Yongshou; Zhang, Mengchuang; Liu, Geng; Ma, Shangjun
The scatter of uncertain factors of the planetary roller screw mechanism, which originated from the manufacturing process, has a significant influence on its serving performance. However, this influence remains insufficiently studied. Further, the elastic–plastic contact analysis of the planetary roller screw mechanism with considering the uncertainties needs large numbers of repetitive calculations by traditional finite element method, which is labor intensive and often impractical. In this paper, an uncertain model of the planetary roller screw mechanism, including parameterization and finite element calculation, is established to conduct the elastic–plastic contact analysis automatically. Besides, the finite element method results can be also obtained automatically with the self-compiled flow program and the secondary development platform using the design of experiment method. Then, a mathematic model is applied to value the influence of the uncertain factors on the contact characteristics. The Pareto graphs are plotted to clearly show this sequence of the percent effects of all the uncertain factors. The present work, for the first time, developed an automatic modeling method for analyzing efficiently the uncertain factors of planetary roller screw mechanism, which is worthy in industrial application.